SUMBER DAN OTORITAS HUKUM DALAM PERSFEKTIF ISLAM DAN BARAT - Azhar Azhar (Universitas Islam Negeri Sumatera Utara, 2016)
One of the things that is closely connected with the problem of such certainty is the issue from which it came. By knowing the origin or the source of such laws. Then we will be able to determine the validity of a law. As for the sources of Islamic law is derived from the Shariah bersuber of revelation, then the law is God, that gathered in the Qur'an. And the second is the Apostles, namely piled up in His. While the source of the Western form of legal norms made by the ruler of the State, the legislature, the Senate, judges and legal experts.